Brønsted Acid Catalyzed Intramolecular Hydroarylation for the Synthesis of Cycloalkenyl Selenides and Tellurides. Issue 13 (13th March 2013) - Eom, Dahan; Park, Sangjune; Park, Youngchul; Lee, Kooyeon; Hong, Gilbert; Lee, Phil Ho
Abstract: Trifluoromethanesulfonic acid catalyzed intramolecular hydroarylation of alkynyl selenides and tellurides is developed for the preparation of cycloalkenyl selenide and telluride derivatives through a selective 6‐ and 7‐ endo mode. The cycloalkenyl selenides and tellurides can be easily converted into a wide range of other valuable functionalities, including cyclic olefins, allylic alcohols, enynes, 1, 3‐dienes, and α, β‐unsaturated aldehydes. Abstract : Trifluoromethanesulfonic acid catalyzed intramolecular hydroarylation of alkynyl selenides and tellurides is developed for the preparation of cycloalkenyl selenide and telluride derivatives through a selective 6‐ and 7‐ endo mode. The cycloalkenyl selenides and tellurides can be easily converted into a variety of valuable functionalities, including cyclic olefins, allylic alcohols, enynes, 1, 3‐dienes, and α, β‐unsaturated aldehydes.